NEURODEGENERATION, MICROVASCULAR DYSFUNCTION AND THEIR INTERACTION: ASSOCIATIONS WITH COGNITIVE PERFORMANCE – THE MAASTRICHT STUDY. (June 2022) - Heide, Frank van der; Henry, Ronald; Houben, Alfons; Kroon, Abraham; Kallen, Carla van der; Dagnelie, Pieter; Schram, Miranda; Eussen, Simone; Berendschot, Tos; Schouten, Jan; Webers, Carroll; Greevenbroek, Marleen Van; et al.
Abstract : Objective: The main objective was to investigate whether there was an interaction between retinal nerve fibre layer (RNFL) thickness, an index of neurodegeneration, and retinal venular diameter, an index of microvascular dysfunction, in the associations of RNFL thickness and retinal venular diameter with global cognitive performance, an index of cognitive function. Design and method: We used cross-sectional data from The Maastricht Study (n = 1, 785 participants, 47.8% men, mean age 59 years, and 24.5% with type 2 diabetes [oversampled by design]) and tested for an interaction between RNFL thickness and retinal venular diameter in the non-linear associations of RNFL thickness and retinal venular diameter with global cognitive performance. RNFL thickness was defined as low (lowest quartile) and high (highest three quartiles combined). Retinal venular diameter was defined as wide (highest quartile) and narrow (lowest three quartiles combined). All associations were adjusted for potential confounders (demographic variables and cardiovascular risk factors). In addition, we tested for interaction by hypertension. Results: The association of RNFL thickness with global cognitive performance was modified by retinal venular diameter (Pinteraction = 0.02) and the association of retinal venular diameter with global cognitive performance was modified by RNFL thickness (Pinteraction = 0.02). After full adjustment, low versus high RNFL thickness was associated with lower global cognitive performance in individuals with, but not in individuals without, a wide retinal venular diameter (beta, [95% confidence interval] low versus high RNFL thickness, -0.26 [-0.43; -0.08] versus -0.03 [-0.14; 0.08], respectively); and wide versus narrow retinal venular diameter was associated with lower global cognitive performance in individuals with, but not in individuals without, a low RNFL thickness (-0.27 [-0.47; -0.06] versus 0.01 [-0.11; 0.12], respectively). Hypertension modified the above associations. In stratified analyses, the above associations were stronger in individuals with, versus without, hypertension. Conclusions: In summary, the present population-based study found an interaction between neurodegeneration, estimated from RNFL thickness, and microvascular dysfunction, estimated from retinal venular diameter, in the associations of RNFL thickness and retinal venular diameter with global cognitive performance. Hence, the interaction between neurodegeneration and microvascular dysfunction may contribute to the pathobiology of cognitive dysfunction.